2015
DOI: 10.1007/s12649-015-9410-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Bio-solvents for the Efficient Extraction of Polyphenolic Phytochemicals: Apple Waste Peels as a Case Study

Abstract: Apple peels were used as a model solid matrix for the comparative evaluation of aqueous mixtures of three biosolvents, including ethanol, 2,3-butanediol (butanediol) and glycerol, with regard to polyphenol recovery. The evaluation process was based on a step-by-step optimisation of the extraction, taking into consideration basic factors, including solvent composition, liquid-to-solid ratio and temperature. A further detailed description of the extraction capacity of each solvent was carried out using kinetics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 37 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…This finding suggests that the amount of both glycerol and CD largely defined Y TP within the limits specified by the experimental design (Table 1). With regard to C gl , the results obtained were in accordance with previous investigations, which showed that increases in C gl up to 70% (w/v) favored polyphenol extraction from apple peels [8]. A similar trend was also reported for polyphenol extraction from two Artemisia species, where the higher yield was achieved with 90% (w/v) glycerol [9].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This finding suggests that the amount of both glycerol and CD largely defined Y TP within the limits specified by the experimental design (Table 1). With regard to C gl , the results obtained were in accordance with previous investigations, which showed that increases in C gl up to 70% (w/v) favored polyphenol extraction from apple peels [8]. A similar trend was also reported for polyphenol extraction from two Artemisia species, where the higher yield was achieved with 90% (w/v) glycerol [9].…”
Section: Resultssupporting
confidence: 89%
“…The three independent variables or factors studied were 2-hydroxypropyl-β-cyclodextrin concentration (C CD ), varying between 1% and 13% (w/v), glycerol concentration (C gl ), varying between 0% and 60% (w/v) and temperature (T), varying between 40˝C and 80˝C. Value ranges were chosen on the basis of preliminary experimentation and previous studies [8,9]. Each variable to be optimized was coded at three levels,´1, 0 and 1 ( Table 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…All the LTTMs were used as 70% (v/v) aqueous solutions because water regulates (i) the polarity of the LTTM, providing, in general, higher extraction yields [11], and (ii) the viscosity of the LTTM, allowing for higher diffusivity. Since solid-liquid extraction is governed by diffusion, increased diffusivity results in a shorter time during which the maximum extraction yield can be achieved [20,21].…”
Section: Lttm Synthesismentioning
confidence: 99%
“…Yet, RL/S of 36.2 mL g −1 has also been reported [15]. It should be stressed that optima RL/S determined for polyphenol extraction with conventional solvents may reach up to 100-120 mL g −1 [20,21], but such With respect to C LTTM , it has been suggested that the amount of water required depends on the polarity of the solute (polyphenols), with flavonoid glycosides, such as rutin, being more soluble in LTTMs with a higher water proportion, compared with its aglycone quercetin [12]. On such a ground, it has been supported that the extraction of more polar compounds may require LTTMs with higher water analogy [13].…”
mentioning
confidence: 96%
“…Yet, R L/S of 36.2 mL g −1 has also been reported [15]. It should be stressed that optima R L/S determined for polyphenol extraction with conventional solvents may reach up to 100-120 mL g −1 [20,21], but such high values have never been predicted for polyphenol extraction with LTTMs. As pointed out earlier, a minimum R L/S is always required for sufficient mixing, which would allow for attaining appropriate diffusivity and hence increased extraction yield.…”
mentioning
confidence: 98%